2014
DOI: 10.1364/oe.22.007598
|View full text |Cite
|
Sign up to set email alerts
|

Spiral autofocusing Airy beams carrying power-exponent-phase vortices

Abstract: We propose a new type of noncanonical optical vortex, named "power-exponent-phase vortex (PEPV)". The spiral focusing of the autofocusing Airy beams carrying PEPVs are experimentally demonstrated, and the physical mechanism is theoretically analyzed by using the energy flow and far field mapping. In addition, the influences of the parameters of PEPVs on the focal fields and orbital angular momenta are also discussed. It is expected that the proposed PEPVs and the corresponding conclusions can be useful for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(46 citation statements)
references
References 39 publications
0
36
0
1
Order By: Relevance
“…with other desired complex amplitude distribution, this technique can be used to produce interferograms for nearly any arbitrary field. Such hologram generation technique has been applied to successfully create Laguerre–Gaussian beams, self‐accelerating Airy beams, and power‐exponent phase vortex beams.…”
Section: Mechanism Of Dmdmentioning
confidence: 99%
“…with other desired complex amplitude distribution, this technique can be used to produce interferograms for nearly any arbitrary field. Such hologram generation technique has been applied to successfully create Laguerre–Gaussian beams, self‐accelerating Airy beams, and power‐exponent phase vortex beams.…”
Section: Mechanism Of Dmdmentioning
confidence: 99%
“…Furthermore, to increase the mode distributions of the perfect OV, the elliptic perfect OV has been reported recently, which is regulated via a scaling factor [15,16]. Moreover, by modulating the phase gradient and the phase jump factors, the power-exponent-phase vortex [17] and the remainder-phase optical vortex [18] are generated, respectively. To obtain more diverse OAM distributions, another method is the beam shaping technology [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in more than one dimension the circular Airy (CAi) beams, as radially symmetric beams that possess autofocusing property [29][30][31][32], have stirred wide interest in the past few years. It has been demonstrated that CAi beams can be used to trap and guide microparticles [33,34] and even to produce the so-called bottle beams [35] and light bullets [36]. Similar to the finite-energy Airy beams, CAi beams can also be controlled and manipulated by potentials [37][38][39].…”
Section: Introductionmentioning
confidence: 99%